In the shadow of Vitoria : a history of international law in Spain (1770-1953) - Rasilla, Ignacio de la (Legal history library, 2017)
In the shadow of Vitoria: A history of international law in Spain' (1770-1953) offers the first comprehensive treatment of the intellectual evolution of international law in Spain from the late 18th century to the aftermath of the Spanish Civil War. Ignacio de la Rasilla del Moral recounts the history of the two `renaissances' of Francisco de Vitoria and the Spanish Classics of International Law and contextualizes the ideological glorification of the Salamanca School by Franco's international lawyers. Historical excursuses on the intellectual evolution of international law in the US and the UK complement the neglected history of international law in Spain from the first empire in history on which the sun never set to a diminished and fascistized national-Catholicist state.